2022
DOI: 10.1111/caim.12498
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the relationships among intellectual property strategies, protection mechanisms and outbound open innovation

Abstract: Many articles in the open innovation literature studied the link between intellectual property protection mechanisms and openness, obtaining contrasting results. This paper bridges the literature on protection mechanisms and the one on intellectual property strategy. It leverages three high‐level intellectual property strategies—defensive, collaborative and impromptu—recently defined in the literature to identify how they entail different intellectual property protection mechanisms and approaches to outbound o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…For instance, IP protection is found to be positively linked with inbound OI (Garriga et al, 2013), whereas patent protection is confirmed an effective means to encourage OI participation (Lichtenthaler, 2009; Pateli & Lioukas, 2019). Similarly, studies have highlighted the positive role of appropriation strategy in boosting outbound OI (e.g., Greco et al, 2022). In similar lines, we argue that:Hypothesis Appropriation strategy is positively related to (a) inbound and (b) outbound OI.…”
Section: Meta‐analytic Conceptual Model and Hypothesesmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, IP protection is found to be positively linked with inbound OI (Garriga et al, 2013), whereas patent protection is confirmed an effective means to encourage OI participation (Lichtenthaler, 2009; Pateli & Lioukas, 2019). Similarly, studies have highlighted the positive role of appropriation strategy in boosting outbound OI (e.g., Greco et al, 2022). In similar lines, we argue that:Hypothesis Appropriation strategy is positively related to (a) inbound and (b) outbound OI.…”
Section: Meta‐analytic Conceptual Model and Hypothesesmentioning
confidence: 97%
“…It denotes a firm's use of physical or legal barriers to prevent the unintended knowledge leakage and to capture value from its innovation investment (Wadhwa et al, 2017). Despite some observations that certain appropriation mechanisms can hinder the implementation of OI (e.g., Alexy et al, 2009, see Greco et al, 2022 for a review), it is widely believed that it allows firms to maintain openness of their innovation processes. Specifically, a firm's implementation of appropriation strategy implies to its external partners that it possesses valuable technologies or knowledge and thus can be a potential collaborator (Laursen & Salter, 2014).…”
Section: Meta‐analytic Conceptual Model and Hypothesesmentioning
confidence: 99%
“…Distinct sources of ideas result in different ideation types that demand different approaches to manage these ideas throughout the innovation process (Lindic et al, 2011). Dahlander and Gann (2010) and Greco et al (2022b) mentioned intellectual property rights among the tools a company can exploit to find new ideas and to trade them. Indeed, regardless of its industry, a company may acquire the required knowledge and technology by purchasing equipment, licenses, intellectual property rights and sponsorship agreements, or by attending conferences and specialized fairs (Bigliardi et al, 2021).…”
Section: Ejim 256mentioning
confidence: 99%
“…, 2011). Dahlander and Gann (2010) and Greco et al. (2022b) mentioned intellectual property rights among the tools a company can exploit to find new ideas and to trade them.…”
Section: Toward Open Innovation In the Fashion Industry: A Review Of ...mentioning
confidence: 99%
“…Practitioners and academicians support that firms need to manage IP from top-level design at a strategic level to IP implementation at an operational level [19][20][21]. The strategic side of IP should be distinguished from its operating protection mechanisms, especially when relating to open innovation [22]. As such, the typologies of value appropriation approaches should be focused specifically on strategic planning, as well as the behaviors and acts employed by firms to appropriate value from the external world [23].…”
Section: Introductionmentioning
confidence: 99%